Pengaruh Pendapatan dan Pola Konsumsi Terhadap Kesejahteraan Keluarga Nelayan di Desa Bunutan Kecamatan Abang - I Nyoman Dedi Arimawan; I Wayan Suwendra (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
This research has been conducted to determine (1) the effect of income on the welfare of fishermen families in Bunutan Village, Abang District, (2) the influence of consumption patterns on the welfare of fishermen families in Bunutan Village, Abang District, (3) the influence of income and consumption patterns on the welfare of fishermen families in Bunutan Village, Abang District. This research has been categorized as causal research. The number of samples involved in this research were 285 respondents. The data was collected using a questionnaire method, analyzed using multiple linear regression, which includes the t-test and F test with the help of the SPSS 16.0 for windows program. The results showed that: (1) there is a positive and significant influence of income on the welfare of fishermen families in Bunutan Village, Abang District partially, this is evidenced by a significance value of 0.000 < 0.05, then H0 is rejected, (2) there is a positive and significant effect of the consumption patterns on the welfare of fishermen families in Bunutan Village, Abang District partially, this is evidenced by a significance value of 0.000 < 0.05, then H0 is rejected, and (3) there is a positive and significant effect of income and consumption patterns on the welfare of fishermen families in Bunutan Village District Simultaneously, this is proven by the significance value of 0.000 < 0.05, then H0 is rejected. The magnitude of the influence of income and consumption patterns on fishermens' families' welfare in Bunutan Village, Abang District, is 52.2%. The coefficient of determination of 0.522 proves this result.